The Study of Overweight and Obesity Predictors in Children Beginning Elementary School in Rasht City - Nasrin Mokhtari (Journal of Global Pharma Technology, 2017)
چمقدمه : نحوه ارتباط والدین با فرزندان با سبک فرزندپروری آنان ارتباط دارد.سبکهای فرزندپروری نقش مهمی در شکل گیری شخصیت بهنجار و نابهنجار در کودکان داشته و در صورت بکار گیری سبکهای ناکارآمد در تربیت کودکان می تواند منجر به پیامدهای منفی متعددی از جمله مشکلات رفتاری در آنان گردد.Introduction: Overweight and obesity is one of health related problems that its prevalence in developed and developing countries is on rise and has become a public health problem. Objective: This study aimed to determine the predictors of overweight and obesity in children beginning elementary schools in the city of Rasht. Methods: This descriptive cross - sectional study was conducted on 426 children aging 6-7 years old, who were selected by stratified randomized method from two districts of Rasht city from all children who referred to National program of children health measurement. Data collection instrument consisted of a researcher made questionnaire to assess predictors of overweight and obesity and sample’s demographic characteristics. Data were analyzed using t-test and ANOVA and Pearson correlation test.Rیافته ها: نتایج نشان داد که سبک فرزندپروری مقتدرانه هم با نمره کل مشکلات رفتاری درونی سازی (003/RResults: The results showed that 8.6% of boys and 14 percent of children were overweight and 19% of boys and 15.3% of girls were obese. There was a positive relationship between children’s overweight and obesity with family history of obesity (p<0.001), maternal BMI (p<0.02), amount of food eaten in comparison with same age children (p<0.001) and the amount of physical activity for children (p=0.02).Conclusions: Four variables of family history of obesity, maternal body mass index, and parents’ view on food taken compared with other children of the same age and hours of physical activity were shown as predictors of overweight and obesity in children entering elementary school. Keywords: Overweight, Pediatric Obesity, Child.